Erak's ransom - Flanagan, John (John Anthony) (New York : Philomel Books, 2010)
On a mission to pay the ransom of a new ally, apprentice Will and his friends find themselves in a desert wasteland awash with enemies.
Wilson's Junior High School, October 2010.
Horn Book, October 2010.
6.1
5-8
850L
Keywords: Apprentices -- Juvenile fiction; Deserts -- Juvenile fiction; Apprentices -- Fiction; War -- Fiction; Deserts -- Fiction; Fantasy; Heroes -- Fiction; Fantasy fiction; War stories